Nurturing bonds that empower learning: a systematic review of the significance of teacher-student relationship in education - Di Lisio, Giulia; Milá Roa, Antonio; Halty, Amaia; Berástegui, Ana; Couso Losada, Alba; Pitillas, Carlos (Frontiers in Education, 2025)
BackgroundTeachers are regarded as attachment-like figures, with positive and supportive teacher-student relationships (TSRs) being linked to improved academic performance and outcomes, while negative TSRs are associated with lower academic results. This systematic review aims to map the relational dimensions of the TSR and its impact on academic (dis)engagement, (under)achievement and early school leaving (ESL), focusing on Secure Base and Safe Haven attachment dimensions and the influence of vulnerability factors.MethodsThe review followed the PRISMA guidelines and included 45 empirical quantitative studies (2018–2022) sourced from Academic Search Complete, ERIC, Scopus and Web of Science. Inclusion criteria were English-written quantitative methodology studies, with TSR as the independent variable and academic outcomes as the dependent variable. Exclusion criteria included longitudinal designs, purely qualitative studies, correlational analyses, studies lacking key variables or presenting reversed relationships, those conducted in e-learning environments, university settings, extreme schooling conditions and non-English language studies. A descriptive and narrative style analysis was used to synthesize the results based on Safe Haven, Secure Base and Global dimensions.Results and discussionKey findings highlighted the significant role of TSR in influencing academic engagement, achievement, and ESL, particularly from vulnerable populations. The synthesis of results indicated that positive TSRs are associated with improved academic outcomes, while negative TSRs can exacerbate disengagement and underachievement. Limitations of the evidence included potential publication bias and the lack of quality control measures, as well as the exclusion of longitudinal and qualitative studies. The findings underscore the significance of a holistic understanding of the TSR in education, highlighting its multifaceted impact on student success and suggesting that future research should consider qualitative and longitudinal studies and expand the scope to studies in non-English language.